2015
DOI: 10.3899/jrheum.150379
|View full text |Cite
|
Sign up to set email alerts
|

Hydroxychloroquine Blood Levels in Systemic Lupus Erythematosus: Clarifying Dosing Controversies and Improving Adherence

Abstract: OBJECTIVES Hydroxychloroquine is used for its effect on systemic lupus erythematosus (SLE) disease activity and long-term benefits. This can be limited by adherence. One way to assess adherence is to measure blood levels. Conflicting data exist regarding blood levels and disease activity. There is dosing controversy; rheumatologists recommend weight-based, while ophthalmologists advocate height-based ‘ideal body weight’ dosing. METHODS Patients were prescribed hydroxychloroquine not to exceed 6.5mg/kg (max40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
179
3
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 161 publications
(197 citation statements)
references
References 47 publications
12
179
3
3
Order By: Relevance
“…A retrospective study of 2361 patients taking HCQ found that actual body weight correlated with risk of retinopathy 1 . In a similar fashion, a prospective study of 300 patients taking HCQ found that actual body weight strongly correlated with blood levels of HCQ 7 , a finding that is corroborated by the study by Durcan, et al 4 . As stated in the editorial, no study has yet definitively linked high blood concentration of HCQ to retinal toxicity 8 , but higher doses and longer durations of therapy have been linked to risk for HCQ retinopathy 1,9 , suggesting that cumulative dose may be a significant risk factor for HCQ retinopathy.…”
Section: To the Editorsupporting
confidence: 69%
See 3 more Smart Citations
“…A retrospective study of 2361 patients taking HCQ found that actual body weight correlated with risk of retinopathy 1 . In a similar fashion, a prospective study of 300 patients taking HCQ found that actual body weight strongly correlated with blood levels of HCQ 7 , a finding that is corroborated by the study by Durcan, et al 4 . As stated in the editorial, no study has yet definitively linked high blood concentration of HCQ to retinal toxicity 8 , but higher doses and longer durations of therapy have been linked to risk for HCQ retinopathy 1,9 , suggesting that cumulative dose may be a significant risk factor for HCQ retinopathy.…”
Section: To the Editorsupporting
confidence: 69%
“…Currently, primary prevention consists of controlling the daily dose and/or cumulative dose to prevent overdosage 3 . We therefore read with great interest "Hydroxychloroquine Blood Levels in Systemic Lupus Erythematosus: Clarifying Dosing Controversies and Improving Adherence" by Durcan, et al 4 in The Journal of Rheumatology. We point out the implications of their findings for the use of weight-based dosing and the evidence base for HCQ retinopathy prevalence.…”
Section: To the Editormentioning
confidence: 99%
See 2 more Smart Citations
“…The results of these analyses are shown in Table 1 of our study 2 and will help to answer many of the issues raised by Weinlander, et al…”
Section: To the Editormentioning
confidence: 85%